2021
DOI: 10.3390/f12060799
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Outbreaks of Defoliating Insects Highlight Growing Threats for Central European Forests, and Implications for Eastern Baltic Region

Abstract: To identify general patterns in the effect of climate-driven changes in the outbreak frequency of forest defoliating species, we examined 60 years of records (1950–2010) of outbreaks of five defoliating species. Data on Lymantria dispar, Lymantria monacha, Bupalus piniarius, Panolis flammea, and Operophtera brumata from five Central European countries (Slovakia, Czech Republic, Austria, Hungary, and Germany), where the current climate is comparable with the projections of climate for the Eastern Baltic region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our study revealed that treatment with Foray 76B may indirectly contribute to C. arcensis decline. Nevertheless, the proliferation of L. monacha outbreaks in recent years [ 25 ] could have a serious impact on C. arcensis populations in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that treatment with Foray 76B may indirectly contribute to C. arcensis decline. Nevertheless, the proliferation of L. monacha outbreaks in recent years [ 25 ] could have a serious impact on C. arcensis populations in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The nun moth ( Lymantria monacha L.) is an important pest of Scots pine forests in central and northern Europe [ 20 , 21 ], expanding its distribution northward and causing frequent outbreaks [ 22 ]. Forests in Poland, the Czech Republic, and Germany [ 20 , 23 ], as well as in Lithuania and Latvia [ 24 , 25 ] experience frequent nun moth outbreaks. Since Scots pine stands provide habitats for many organisms, the spread of L. monacha can reduce their abundance or even threaten some species [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This increases tree mortality not only directly through drought and heat stress [ 3 , 4 ] but also indirectly by increasing their susceptibility to pests and pathogens [ 5 ]. Simultaneously, accelerating warming is promoting some insect development and outbreaks due to earlier food supplies and longer growing seasons [ 6 ]. These include Lepidoptera (moths and butterflies), which are commonly known as one of the most important groups of herbivores and pollinators, containing a huge vast prey biomass and hosting an extensive specialized web of parasitic Hymenoptera, and playing an important role in the functioning of our ecosystems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pest outbreaks have been observed since the 18th century [11], with the latest outbreak in 2018-2020 where more than 3500 ha of pine stands were damaged [12]. The outbreaks of L. monacha also occur periodically in other Central and Northern European countries, including Poland [13], the Czech Republic [14], Germany [9], and Latvia [6]. The expansion of L. monacha infestations is marked by high population densities of the larvae [15], which feed on coniferous tree needles, removing the photosynthetic tissue critical for plant maintenance and growth [16].…”
Section: Introductionmentioning
confidence: 99%
“…In its native range in temperate Europe and Asia, it can cause severe damage during outbreaks, though it is mostly known for its severe impacts and rapid expansion in North American forests, where it is invasive (McManus and Csóka, 2007). Over the last decades, severe defoliation events, range expansion, and increasing outbreak frequencies have been reported across Central Europe (Zúbrik et al, 2021;McManus and Csóka, 2007;Silin ¸š et al, 2021), Russian Far East and Central Asia (Gninenko and Orlinskii, 2003;Orozumbekov et al, 2009) and North Africa (Villemant and Ramzi, 1995).…”
Section: Introductionmentioning
confidence: 99%